Implementation of Process Innovation and Product Innovation to Improve Operational Performance at the Batik Production House "Uni Batik" in Surakarta City, Central Java - Putri , Wina Dahlia; Abdillah, Willy (Student Journal of Business and Management, 2024)
The purpose of thus study was to analyze whether process innovation and product innovation can improve operational performance at the Batik Production House “Uni Batik” in Surakarta, Center of Java. The type of research used is qualitative research, with a research design that is semi-structured interview design and direct observation. The data used is in the form of primary data and secondary data. The informants consisted of one key informant and one key informant. The analytical method used is content analysis method which is qualitative in nature. The resulting data is a 'thick description' or an in-depth interpretation that is based on a real context. The interview results were transcribed using true verbatim transcripts. The results of this study explain that the process innovation carried out at Uni Batik uses a measurement method based on the OECD, by assessing the level of efficiency of the production process, the quantity and quality of the products produced, the accuracy of the delivery process, and the level of production costs. Product innovation carried out at Uni Batik uses 6 stages of the product innovation process. Therefore, with the implementation of process innovation and product innovation, direct benefits can be felt in the form of increased productivity and operational performance of the company as a whole.